Solve the equation?

Solve the equation

2x^2 + 8x - 1 = 0

by completing the square

7 Answers

Relevance
  • 1 month ago

    2x^2 + 8x - 1 = 0

    2/9 (x + 2)^2 = 1

    Solutions:

    x = -2 - 3/sqrt(2)

    x = 3/sqrt(2) - 2

  • 1 month ago

    The answer is Yes.

  • Philip
    Lv 6
    1 month ago

    2x^2+8x-1=0, ie., 2x^2+8x-1+9=9, ie., 2(x^2+4x+4) =9, ie., (x+2)^2 =[(3/2)rt2]^2.

    Then x = -2(+/-)(3/2)rt2, where rt2 = sqrt2.

  • sepia
    Lv 7
    1 month ago

    2 x^2 + 8 x - 1 = 0

    2/9 (x + 2)^2 = 1

    Solutions:

    x = -2 - 3/sqrt(2)

    x = 3/sqrt(2) - 2

  • How do you think about the answers? You can sign in to vote the answer.
  • 1 month ago

    2x² + 8x - 1 = 0

    Here's how I solve this by completing the square.  Start with making the left half of the equation be in the form of (x² + bx).  We'll add 1 to both sides then divide both sides by 2:

    2x² + 8x = 1

    x² + 4x = 1/2

    Now that we have the form we need, the "complete the square" step is done by following these steps:

    Start with x's coefficient (4)

    half it (2)

    square it (4)

    Add that to both sides of the equation:

    x² + 4x + 4 = 1/2 + 4

    The left side is now a perfect square trinomial that can be factored and the right side can be simplified:

    (x + 2)² = 1/2 + 8/2

    (x + 2)² = 9/2

    Square root of both sides:

    x + 2 = ± √(9/2)

    Subtract 2 from both sides, then simplify the radical, including rationalizing the denominator:

    x = -2 ± √(9/2)

    x = -2 ± 3/√2

    x = -2 ± (3/2)√2

  • Amy
    Lv 7
    1 month ago

    Divide by the x^2 coefficient.

    x^2 + 4x - 1/2 = 0

    Complete the square

    (x^2 + 4x + 4) - 4 - 1/2 = 0

    (x+2)^2 - 4 - 1/2 = 0

    Solve for x

    (x+2)^2  = 4.5

    x+2 = ±√4.5

    x+2 = ± 3√2/2

    x = -2 ± 3√2/2

  • 1 month ago

    2x² + 8x - 1 = 2(x² + 4x) - 1

    i.e. 2(x + 2)² - 8 - 1

    Hence, 2(x + 2)² - 9 = 0

    so, 2(x + 2)² = 9    

    => (x + 2)² = 9/2

    so, x + 2 = ±3/√2 => ±3√2/2

    i.e. x = -2 ± 3√2/2 => (-4 ± 3√2)/2

    Hence, x = (-4 + 3√2)/2 or -(4 + 3√2)/2

    :)>

Still have questions? Get your answers by asking now.